2004
DOI: 10.1080/0964401042000209630
|View full text |Cite
|
Sign up to set email alerts
|

‘Obstruction Galore’: A Case Study of Non-violent Resistance Against Nuclear Waste Disposal in Germany

Abstract: The X-tausendmal quer (Obstruction Galore) campaign was one of the most important non-violent anti-nuclear resistance campaigns in Germany. A theoretical framework derived from political process theory is employed in order to analyse the campaign. The activities of the X-tausendmal quer campaign since its foundation in 1996 are examined in the context of changing political opportunities, especially with the election victory of the Red-Green coalition in 1998. The successes and failures of Xtausendmal quer are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Studies have found that activists persevere (Abramowitz & Nassi, 1981;Downton & Wehr, 1998;Einwohner, 2002;Fendrich, 1977;Fendrich & Smith, 1980;Fischer & Boehnke, 2004;Nassi & Abramowitz, 1979;Stewart, Settles, & Winter, 1998; Van Dyke & Dixon, 2013) more than non-activists through their activism (Fendrich & Lovoy, 1988;Fendrich & Tarleau, 1973;McAdam, 1989). In a study of 223 civil rights activists from 1965 that participated in the Southern Christian Leadership Conference led by Martin Luther King Jr., Marwell et al (1987) interviewed participants four years later, and again in 1984.…”
Section: Sustained Commitmentmentioning
confidence: 99%
“…Studies have found that activists persevere (Abramowitz & Nassi, 1981;Downton & Wehr, 1998;Einwohner, 2002;Fendrich, 1977;Fendrich & Smith, 1980;Fischer & Boehnke, 2004;Nassi & Abramowitz, 1979;Stewart, Settles, & Winter, 1998; Van Dyke & Dixon, 2013) more than non-activists through their activism (Fendrich & Lovoy, 1988;Fendrich & Tarleau, 1973;McAdam, 1989). In a study of 223 civil rights activists from 1965 that participated in the Southern Christian Leadership Conference led by Martin Luther King Jr., Marwell et al (1987) interviewed participants four years later, and again in 1984.…”
Section: Sustained Commitmentmentioning
confidence: 99%
“…Throughout this period there has been a continuing flow of case studies that have addressed resistance and stalemates against HLW disposal. Some examples are risk communication in the search for underground laboratory sites in France (Barthe and Mays 2001), the nonviolent resistance against radioactive waste disposal in Germany (Fischer and Boehnke 2004), psychological factors regarding HLW facility sitings in Japan (Tanaka 2004;Kugo et al 2008) and South Korea (Chung et al 2008), and the multiple causes of the ultimate failure of the Yucca Mountain project in the United States (Ewing and von Hippel 2009). Thus, a wide range of aspects of HLW management has continued to be scrutinized in the last 15 years.…”
Section: From Political Stalemate To Real Solutions?mentioning
confidence: 99%
“…As commercial nuclear power entered its sixth decade in the mid-1990s, no country anywhere in the world, including Western Europe, had opened a repository for the final disposal of SNF and HLWs, or cleared the political and legal obstacles to doing so. Where European governments attempted to announce the selection of a repository site "from above," the resulting explosion of local and national opposition prompted either a quick retreat or, as in Germany, a protracted conflict that further galvanized the antinuclear movement (Fischer and Boehnke 2004). 11 More often, European governments simply avoided precipitous action, kicking the problem down the road for another government on another day.…”
Section: Siting In Limbo: Nuclear Power and Radioactive Waste Disposamentioning
confidence: 99%